Analysis of the Impact of Online Gambling Addiction on Adolescent in Pabelan Village, Kartasura Subdistrict, Sukoharjo Regency - Trisnandi Trisnandi; Titik Ulfatun (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Changes in the pattern of life of each individual today begin with a new era where there is an influence from the development of technology which is quite rapid and can be reflected through their interaction with the surrounding environment. This is one of the triggers for changes in habits, especially for adolescents in Pabelan Village, Kartasura District, Sukoharjo Regency in using technology, one of which is the use of technology in negative terms, namely playing online gambling. The purpose of this research is to describe the reasons and how the impact of online gambling addiction is carried out by teenagers in Pabelan Village, Kartasura District, Sukoharjo Regency. The type of research used is qualitative with a case study approach. This research was conducted in Pabelan Village, Kartasura District, Sukoharjo Regency and the research was conducted from December 2023 to February 2024. The main informants of this research are 3 teenagers in Pabelan Village, Kartasura District, Sukoharjo Regency. The instruments used in this research are interview guidelines, observation and documentation. Data collection techniques were carried out by in-depth interviews and document studies. Data analysis of this research is by data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that online gambling addiction in adolescents has a broad and serious impact. These impacts include social, economic, educational, and health. Various factors such as socio-economic status, socialization, and perceptions of victory exacerbate these impacts. Therefore, attention and effective prevention efforts are needed to address this problem. Parents should pay more attention to their children and create a loving environment. With the cooperation of various parties, adolescents can be protected from the dangers of online gambling. Keywords: Online gambling, Adolescent, Addiction